Climate Change and Ecosystems - National Academy of Sciences (The National Academies Press, 2019)
The National Academies convened a forum on November 8-9, 2018 to highlight current research frontiers such as the effects of climate extremes, interactions among climate and other stressors, the timing, sequence, and clustering of climate-related events, and tipping points for abrupt change. Topics of discussion at the forum pertained to the changes ecosystems are currently undergoing, sustaining ecosystems, the impact of ecosystems on global climate change, societal adaptation to climate change, and priorities for future research. This report summarizes the presentations and discussions from the forum.
Keywords: Environment and Environmental Studies

Making Climate Assessments Work: Learning from California and Other Subnational Climate Assessments: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Climate assessment activities are increasingly driven by subnational organizations—city, county, and state governments; utilities and private companies; and stakeholder groups and engaged publics—trying to better serve their constituents, customers, and members by understanding and preparing for how climate change will impact them locally. Whether the threats are drought and wildfires, storm surge and sea level rise, or heat waves and urban heat islands, the warming climate is affecting people and communities across the country. To explore the growing role of subnational climate assessments and action, the National Academies of Sciences, Engineering, and Medicine hosted the 2-day workshop on August 14-15, 2018. This publication summarizes the presentations and discussions from the workshop.
Keywords: Environment and Environmental Studies

21st Century Paradigm Change in Performance and Design Metrics: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In September 2015, the National Academies of Sciences, Engineering, and Medicine convened a two-day workshop on evolving paradigms for design and manufacturing. Participants discussed ways to lower costs and shorten production time in defense systems while bringing materials and manufacturing alternatives into the tradespace. This publication summarizes the presentations and discussions from the workshop.
Keywords: Conflict and Security Issues

Strengthening the Connection Between Health Professions Education and Practice: Proceedings of a Joint Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On November 13 and 14, 2018, members of the National Academies of Sciences, Engineering, and Medicine’s Global Forum on Innovation in Health Professional Education participated in a joint workshop with affiliates of the National Center for Interprofessional Practice and Education. The workshop participants explored the intersection of health professions education and practice. Both sectors are working toward the same goal of improving the health of patients and populations, without compromising the mental stability and wellbeing of the workforce or its learners. However, while education and practice have the same goal, there is a need for greater alignment between the sectors to more fully realize these desired outcomes. For example, educators, practitioners, and administrators must learn to adapt and respond to the growing role of technology within a wider context, in order to most effectively apply higher education within health systems. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

A Design Thinking, Systems Approach to Well-Being Within Education and Practice: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The mental health and well-being of health professionals is a topic that is broad, exceptionally relevant, and urgent to address. It is both a local and a global issue, and affects professionals in all stages of their careers. To explore this topic, the Global Forum on Innovation in Health Professional Education held a 1.5 day workshop. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Education

Exploring Early Childhood Care and Education Levers to Improve Population Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On September 14, 2017, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore the intersection of health and early childhood care and education, two key social determinants of health. This workshop follows a 2014 roundtable workshop that considered the interface between the education and health sectors broadly, from research and metrics to cross-sectoral partnerships and financing. The 2017 workshop continued that discussion, with a deeper focus on early childhood (birth through age 5) as a critical period in human development and an important opportunity for educational and related interventions. This publication summarizes the presentations and discussions from the 2017 workshop.
Keywords: Health and Medicine

Second International Summit on Human Genome Editing: Continuing the Global Discussion: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
On November 27-29, 2018, the U.S. National Academy of Sciences and U.S. National Academy of Medicine, the Royal Society of the United Kingdom, and the Academy of Sciences of Hong Kong convened the Second International Summit on Human Genome Editing at the University of Hong Kong. The summit brought together more than 500 researchers, ethicists, policymakers, representatives from scientific and medical academies, patient group representatives, and others from around the world. Over the two-and-a-half-day event, topics including the potential benefits and risks of human genome editing, ethical and cultural perspectives, regulatory and policy considerations, and public outreach and engagement efforts were explored. This publication summarizes the presentations and discussions from the event.
Keywords: Biology and Life Sciences; Policy for Science and Technology

Climate Communications Initiative Strategic Plan - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Keywords: Environment and Environmental Studies; Policy for Science and Technology

Climate Resilience and Benefit–Cost Analysis: A Handbook for Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Report 199: Climate Resilience and Benefit–Cost Analysis: A Handbook for Airports provides information on how to apply benefit–cost analysis tools and techniques to improve decision making affecting resilience of airport infrastructure projects in response to potential long-term impacts of climate change and extreme weather events.The handbook is designed to improve the process by which infrastructure investment strategies are evaluated, with an emphasis on ensuring climate-related resiliency.Procedures for presenting assumptions and results transparently and for implementing the process are also included so that industry users and decision makers can understand and communicate the outcome of the analytical process.Based on data availability, the analytical methods included in the handbook focus on two specific areas of climate change likely to affect airports (although these methods can, in principle, be used more widely): (1) the potential for extreme flooding events resulting from storm surge and sea level rise near coastal airports, and (2) the potential for rising temperatures that require weight restrictions on aircraft takeoffs (or possibly full flight delays) at airports with shorter runways in warm climates or at high elevations.The results available from application of the suggested methodologies do not necessarily make the decision of whether to invest in a mitigation project to combat climate change any easier but, rather, provide a full range of potential outcomes and possibilities for airport planners and managers to consider. Using this methodology, airport decision makers can then determine how much risk from uncertain climate change and extreme weather events they are willing or able to accommodate. Implementation of the methods presented in the handbook can be used to obtain essential quantifiable estimates of those risks, which is of particular value to airport financial professionals.The handbook is accompanied by a set of Microsoft Excel models to support the decision-making process (one for extreme water rise causing potential flooding events, and the other for high temperatures that may affect weight restrictions on aircraft takeoffs), a video tutorial, a report summary document, and an executive briefing to help decision makers understand the process.
Keywords: Transportation and Infrastructure

Promoting Aviation Career Education in High Schools and Community Colleges - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
More airport operations/management academic programs at both the high school and community college levels would help the airport industry. With baby boomers currently reaching retirement age at the rate of 10,000 each day, and later generations much smaller in size, new employees are not entering the workforce swiftly enough to replace those leaving because of retirement, illness, and other complicating factors.As a result, the aviation industry, like others, is experiencing a significant labor shortage. With no end in sight, the industry has joined forces in a number of unique partnerships in an effort to not only enhance the quality of current aviation graduates, but also stimulate interest in aviation careers among college students, high school students, and even middle school and elementary school students.The TRB Airport Cooperative Research Program's ACRP Synthesis 103: Promoting Aviation Career Education in High Schools and Community Colleges points out the many characteristics of high school and community college aviation programs throughout the country, which could prove useful to airport management. By better understanding the academic programs producing the next generation of aviation professionals, airports can develop proactive efforts to promote the airport profession to aviation programs in their local area and influence young people to seriously consider airports as a viable career path, thus positively affecting the future of the airport industry.
Keywords: Transportation and Infrastructure

Developing Innovative Strategies for Aviation Education and Participation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Resources to help promote interest in aviation among younger populations ranging from 10 years old to 25 years old are detailed in TRB’s Airport Cooperative Research Program (ACRP) Research Report 202.The report is designed to help educators and aviation enthusiasts understand the need for encouraging interest in aviation. It offers guidance on developing a program of activities to fit particular needs and provides activities for developing a program that can be scaled and tailored for various age groups and resource availability.The report is designed to help develop intentional pathways for promoting interest in aviation. These pathways are seen as the process for engaging students at an early age to pursue aviation at some level and then have them, in turn, continue the cycle by promoting aviation to others.The report addresses the challenges to establishing and maintaining these pathways—such as resource limitations, lack of programming or curriculum, competing interests for kids, and administrative or organizational issues—and identifies opportunities to overcome them.The report also provides support for developing and executing single events and activities when they are the most practical means for exposing young people to the aviation industry. Finally, the report includes three summary listings of the landing pages. The landing pages are a collection of activities that can engage young people in aviation and be adapted to any particular group or organization. They are sorted by activity type, target age group, and cost per person. A searchable list, by keyword, of these landing pages can be found in the Presorted Tables PDF.There is also an individual activity landing pages PDF, which is an alphabetical listing of organizations and the types of activities they offer. The PDF User Guide explains how to use and search the PDFs. A microsite with the Presorted Tables PDF, the Individual Activity Landing Pages PDF, and the PDF User Guide may be found at http://www.trb.org/acrp/acrpreport202.aspx.
Keywords: Transportation and Infrastructure

Thought Leader Forum Summary—Emerging Issues for ACRP - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
TRB’s Airport Cooperative Research Program (ACRP) Research Results Digest 28: Thought Leader Forum Summary—Emerging Issues for ACRP summarizes a January 30, 2019, forum to identify the most important issues facing the airport industry within the next 5 to 10 years.The goal of this exercise was to engage the ACRP’s Airport Operations Committee (AOC) directly with other thought leaders in the industry to identify and define high-level emerging critical issues that impact, or will soon impact, the airport industry.The digest describes the results of a pre-Forum survey designed to help shape the Forum discussion, summarizes the results of the forum itself, and explores potential next steps.
Keywords: Transportation and Infrastructure

Acquisition Strategies for Future Space-Based Optics: Unclassified Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
This study originated with congressionally directed language from the House Permanent Select Committee for Intelligence (HPSCI) in 2016 and titled “Acquisition Strategies for Future Space Based Optics”. This publication is an unclassified summary of the classified report.
Keywords: Conflict and Security Issues; Space and Aeronautics

The Growing Threat to Air Force Mission-Critical Electronics: Lethality at Risk: Unclassified Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
High-performance electronics are key to the U.S. Air Force’s (USAF’s) ability to deliver lethal effects at the time and location of their choosing. Additionally, these electronic systems must be able to withstand not only the rigors of the battlefield but be able to perform the needed mission while under cyber and electronic warfare (EW) attack. This requires a high degree of assurance that they are both physically reliable and resistant to adversary actions throughout their life cycle from design to sustainment. In 2016, the National Academies of Sciences, Engineering, and Medicine convened a workshop titled Optimizing the Air Force Acquisition Strategy of Secure and Reliable Electronic Components, and released a summary of the workshop. This publication serves as a follow-on to provide recommendations to the USAF acquisition community.
Keywords: Conflict and Security Issues

Evaluating the Taxonomic Status of the Mexican Gray Wolf and the Red Wolf: Spanish-Language Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Scientists strive to develop clear rules for naming and grouping living organisms. But taxonomy, the scientific study of biological classification and evolution, is often highly debated. Members of a species, the fundamental unit of taxonomy and evolution, share a common evolutionary history and a common evolutionary path to the future. Yet, it can be difficult to determine whether the evolutionary history or future of a population is sufficiently distinct to designate it as a unique species. A species is not a fixed entity – the relationship among the members of the same species is only a snapshot of a moment in time. Different populations of the same species can be in different stages in the process of species formation or dissolution. In some cases hybridization and introgression can create enormous challenges in interpreting data on genetic distinctions between groups. Hybridization is far more common in the evolutionary history of many species than previously recognized. As a result, the precise taxonomic status of an organism may be highly debated. This is the current case with the Mexican gray wolf (Canis lupus baileyi) and the red wolf (Canis rufus), and this publication provides a spanish-language summary of the assessment of the taxonomic status for each.
Keywords: Biology and Life Sciences

Fostering the Culture of Convergence in Research: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Convergence-based research approaches are critical in solving many scientific challenges, which frequently draw on large teams of collaborators from multiple disciplines. The 2014 report Convergence: Facilitating Transdisciplinary Integration of Life Sciences, Physical Sciences, Engineering, and Beyond describes the term “convergence” as a multidisciplinary approach that melds divergent areas of expertise to form conclusions that are inaccessible otherwise. However, a convergence-based approach involves hybrid systems of people, buildings, and instruments, which pose complex structural and managerial challenges. In October 23–24, 2018, the National Academies of Sciences, Engineering, and Medicine convened a workshop to explore efforts to promote cultures that support convergence-based approaches to research. The 2014 report served as a foundation for this workshop, allowing participants to further explore convergence as a valuable and adaptable approach to organizing research. This publication summarizes the presentations and discussions from the workshop.
Keywords: Policy for Science and Technology

Together We Can Do Better: A Gathering of Leaders in Academia to Prevent Sexual Harassment: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In recent decades, important gains have been made with respect to the participation of women in science, technology, engineering, and medical (STEM) disciplines at the undergraduate and graduate levels in the United States. More women than ever are joining faculty ranks in these fields and moving into leadership positions in higher education. While the “gender gap” is narrowing, the National Academies of Sciences, Engineering, and Medicine report Sexual Harassment of Women: Climate, Culture, and Consequences in Academic Sciences, Engineering, and Medicine argues that more rapid and sustained progress in closing the gap in science, engineering, and medicine is jeopardized by the persistence of sexual harassment and its adverse impact on women’s careers at colleges and universities. In an effort to advance the discussion on implementing the report’s recommendations, the National Academies held a convocation on November 9, 2018 in Washington, DC. The event brought together academic leaders, Title IX and diversity officers, ombudsmen, researchers in sexual harassment, and leaders from professional societies, foundations, and federal agencies, to discuss strategies and share promising practices. This publication summarizes the presentations and discussions from the convocation.
Keywords: Education

The Transformational Impact of 5G: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The fifth generation of wireless networks and technologies presents significant opportunity to transform connectivity. Improvements in bandwidth, latency, coverage, reliability, and security can enable an array of enhanced and new applications. On June 11-12, 2019, the National Academies of Sciences, Engineering, and Medicine convened experts to speak about the state of research, development, and deployment of 5G technologies; the challenges of securing 5G networked devices and infrastructure; and the global landscape of competition on 5G deployment. Priorities for cross sector collaboration and coordination between government, universities, and industry to advance the nation's leadership in wireless communication were also discussed. This publication summarizes the presentations and discussions from the workshop.
Keywords: Computers and Information Technology; Engineering and Technology

Forced Migration Research: From Theory to Practice in Promoting Migrant Well-Being: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In 2018, the United Nations High Commissioner for Refugees estimated 70.8 million people could be considered forced migrants, which is nearly double their estimation just one decade ago. This includes internally displaced persons, refugees, asylum seekers, and stateless people. This drastic increase in forced migrants exacerbates the already urgent need for a systematic policy-related review of the available data and analyses on forced migration and refugee movements. To explore the causes and impacts of forced migration and population displacement, the National Academies convened a two-day workshop on May 21-22, 2019. The workshop discussed new approaches in social demographic theory, methodology, data collection and analysis, and practice as well as applications to the community of researchers and practitioners who are concerned with better understanding and assisting forced migrant populations. This workshop brought together stakeholders and experts in demography, public health, and policy analysis to review and address some of the domestic implications of international migration and refugee flows for the United States. This publication summarizes the presentations and discussions from the workshop.
Keywords: Behavioral and Social Sciences

Understanding Northern Latitude Vegetation Greening and Browning: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Vegetation change has been observed across Arctic and boreal regions. Studies have often documented large-scale greening trends, but they have also identified areas of browning or shifts between greening and browning over varying spatial extents and time periods. At the same time, though, there are large portions of these ecosystems that have not exhibited measurable trends in greening or browning. These findings have fueled many questions about the drivers of vegetation dynamics, how trends are measured, and potential implications of vegetation change at local to global scales. In December 2018, the National Academies of Sciences, Engineering, and Medicine, convened a workshop to discuss opportunities to improve understanding of greening and browning trends and drivers and the implications of these vegetation changes. The discussions included a close look at many of the methodological approaches used to evaluate greening and browning, as well as exploration of newer technologies that may help advance the science. This publication summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences